Cyto-histopathological correlation of thyroid lesions - Ramteke, Disha J.; Mulay, Prabha S. (International Journal of Research in Medical Sciences, 2017)
Background: Thyroid is a frequent site of disease in human body. Fine needle aspiration cytology is a rapid, efficient, inexpensive and safe diagnostic method in these cases. FNAC has some limitations, particularly limited to representatives of samples and exact typing of benign and malignant neoplastic lesions. Thus, FNAC alone may not give a confirmative diagnosis regarding few thyroid lesions. Hence, histopathological study has been the standard technique for the diagnosis of thyroid lesions. Objectives were to study cytomorphological features of thyroid enlargement and palpable lesions of thyroid by FNAC, to correlate cytomorphological features of thyroid lesions with Histopathological features wherever possible and to evaluate sensitivity and specificity of FNAC of thyroid lesions. Methods: In the present study, 385 cases of thyroid FNA’s, have been analyzed and cyto-histopathological correlation has been interpreted wherever available. Results: In present study sensitivity, specificity, positive predictive, negative predictive value and accuracy of FNAC was found out be 92.31%, 97.01%, 85.71%, 98.48% and 96.25%. Conclusions:Fine needle aspiration cytology is a simple reliable and cost effective technique without complications. This can be used as safe outpatient procedure with minimal discomfort to the patient.